Formulation and Evaluation of Bilayer Tablets of Ramipril as Immediate Layer and Propranolol Hydrochloride as Sustained Layer - Reddy, Dr. M. Sunitha (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The purpose of this research work was to develop a bilayer tablet of antihypertensive drugs having sustained release (SR) layer of propranolol hydrochloride and immediate release (IR) layer of ramipril. Objectives: In the present investigation, an attempt was made to reduce the frequency, units of dose administration, and to improve the patient compliance. Materials and Methods: The tablets were prepared using ethyl cellulose and hydroxypropyl methylcellulose K-15M for sustained layer of propranolol hydrochloride and superdisintegrants crospovidone and sodium starch glycolate for IR layer of ramipril. Preformulation studies of propranolol hydrochloride and ramipril like compatibility studies with polymers using Fourier-transform IR were carried out. The drugs and excipients were found to be compatible with each other. Compressed tablets were evaluated for hardness, thickness, weight variation, friability, drug content, in vitro drug release studies, and stability studies Results and Discussion: Nine batches of bilayer tablets of propranolol hydrochloride and ramipril were developed using wet granulation and direct compression techniques, respectively. Among the nine formulations, F9 batch showed best drug release over 12 h and subjected to stability studies for 2 months. Conclusion: The optimized F9 formulation for IR showed a release of 99.27% and propranolol hydrochloride has an in vitro release of 99.39%. Therefore, bilayer ramipril IR and SR tablets of propranolol hydrochloride can be used to improve the management of hypertension